Lead-free, copper-free tin alloy and solder balls for ball grid array packages

A lead-free, copper-free tin alloy with specific compositions addresses thermal stress and mechanical durability issues in BGA packages by enhancing solder bump reliability through improved mechanical impact resistance and thermal cycling performance.

JP7625565B2Active Publication Date: 2025-02-03SHENMAO TECH INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022184605
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-14
Filing Date
2022-11-18
Publication Date
2025-02-03
Estimated Expiration
2042-11-18

AI Technical Summary

Technical Problem

The existing ball grid array (BGA) packages face issues with thermal stress due to the mismatch in thermal expansion coefficients between the organic substrate and silicon chip, leading to damage at the solder bump junctions, and require improved mechanical durability and reliability in the face of mechanical impacts.

Method used

A lead-free, copper-free tin alloy composition comprising 0.01-3.0 WT% silver, 0.01-5.0 WT% bismuth, 0-2.0 WT% antimony, 0.005-0.1 WT% nickel, and 0.005-0.02 WT% germanium is developed to enhance the mechanical impact resistance, weldability, antioxidant properties, and thermal cycling reliability of solder bumps.

Benefits of technology

The proposed alloy ensures excellent mechanical impact resistance, reliable welding, and effective thermal cycling performance of solder bumps in BGA packages, addressing the limitations of conventional tin alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625565000007
    Figure 0007625565000007
  • Figure 0007625565000008
    Figure 0007625565000008
  • Figure 0007625565000009
    Figure 0007625565000009
Patent Text Reader

Abstract

To provide a lead, copper and tin-free alloy.SOLUTION: A lead, copper and tin-free alloy contains 0.01-3.0 wt.% silver, 0.01-5.0 wt.% bismuth, 0-2.0 wt.% antimony, 0.005-0.1 wt.% nickel, 0.005-0.02 wt.% germanium, and a surplus amount tin. The lead, copper and tin-free alloy has a structure obtained after welding having, for example, reliability to excellent mechanical shock by a solder bump, and simultaneously has good weldability, ductility, antioxidant capability and reliability of heat circulation.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tin alloy and a solder ball for a ball grid array package made from said tin alloy, and more particularly to Lead-free, copper-free tin alloy (alloy without lead, copper, and tin) and the above Lead-free, copper-free tin alloy This relates to solder balls for ball grid array packages manufactured by . [Background technology]

[0002] With the increase in the number of I / Os (input / output) of semiconductor devices, packaging technology that was originally only available for wire bonding, which packages the chips around the periphery, is now also available for ball grid array (BGA) packaging, which packages the chips on the bottom surface. This technology distributes the bonding pads on the bottom of the semiconductor device by performing IC bonding pad re-layout (I / O distribution) on the semiconductor device, increasing the I / O density. Summary of the Invention

[0003] The conductive methods of ball grid array packages are divided into metal bumps, conductive adhesives, conductive films, etc. Solder bumps, which belong to metal bump technology, are the mainstream. Ball grid array packages are divided into non-wafer level packages and wafer level packages.

[0004] In addition, the non-wafer level package refers to a method in which a silicon chip is welded to an organic substrate by wire bonding or flip chip, an underfill is injected between the silicon chip and the organic substrate, and then a solder ball is welded to the other end of the organic substrate to form a solder bump, thereby forming an electronic element. [Problem to be solved by the invention]

[0005] However, due to the large difference in the expansion coefficients between the organic substrate and the silicon chip, when a temperature change occurs in the electronic device itself or in the environment, the thermal stress caused by the mismatch in the coefficient of thermal expansion can damage the welds (solder bumps) between the electronic device and the circuit substrate (there is an underfill at the welds between the organic substrate and the silicon chip, so they normally do not damage).

[0006] Wafer level packaging refers to performing most or all of the package testing process directly on a silicon wafer, then cutting it to produce individual chips, and performing IC bonding pad re-layout directly on the chip without an organic substrate, and then welding solder balls to form solder bumps. Since the size of the packaged chip is almost the same as that of the bare chip, it is called wafer level chip scale package (WLCSP). However, since there is a large difference in the expansion rate between the silicon chip and the circuit board, the welding points (solder bumps) that connect the two must be able to withstand thermal stress when the electronic device itself or the environment changes in temperature. In addition, since many wafer level packages are applied to lightweight, thin, and small mobile devices, the welding points (solder bumps) must have high resistance to mechanical shock.

[0007] The main properties required for conventional tin alloys are alloy strength and thermal cycling reliability. However, when simultaneously increasing alloy strength and thermal cycling reliability, the ductility of the tin alloy is reduced, and the reliability of the tin alloy against mechanical shock is also reduced.

[0008] Therefore, the current goal of intensive research is to find a tin alloy that can be used to prepare solder balls for use in ball grid array (BGA) packages, and that has good weldability, ductility, oxidation resistance, and thermal cycling reliability while providing a structure (e.g., solder bump) obtained after welding with excellent reliability against mechanical shock.

[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to solve the above problems. Lead-free, copper-free tin alloy The first object of the present invention is to provide the above. Lead-free, copper-free tin alloy is capable of producing solder balls for use in ball grid array (BGA) packages, and Lead-free, copper-free tin alloy The resulting structure (eg, solder bump) after welding has excellent reliability against mechanical shock, while also having good weldability, ductility, oxidation resistance, and thermal cycling reliability.

[0010] Here, the present invention Lead-free, copper-free tin alloy The above Lead-free, copper-free tin alloy of Weight Percent is 100 wt%, and contains 0.01 to 3.0 wt% silver, 0.01 to 5.0 wt% bismuth, 0 to 2.0 wt% antimony, 0.005 to 0.1 wt% nickel, 0.005 to 0.02 wt% germanium, and a surplus amount of tin.

[0011] A second object of the present invention is to provide a solder ball for a ball grid array package.

[0012] Here, the solder ball for a ball grid array package according to the present invention is Lead-free, copper-free tin alloy It is manufactured in. [Means for solving the problem]

[0013] In order to solve the above problems, the present invention provides Lead-free, copper-free tin alloy The above Lead-free, copper-free tin alloy of Weight Percentis 100 wt%, and contains 0.01 to 3.0 wt% silver, 0.01 to 5.0 wt% bismuth, 0 to 2.0 wt% antimony, 0.005 to 0.1 wt% nickel, 0.005 to 0.02 wt% germanium, and a surplus amount of tin.

[0014] The point to be explained here is that Lead-free, copper-free tin alloy The point is that it is substantially free of lead (Pb) and copper (Cu). The above-mentioned "substantially free of lead and copper" means that in principle, lead and copper are not intentionally added to the tin alloy (except for, for example, unintentional unavoidable impurities or contact during the manufacturing process), and therefore, based on the gist of the present invention, it is considered to be substantially free of lead and copper, or to be free of lead and copper. wt% is Weight Percent In this specification, wt% refers to Weight Percent In addition, the limitations of the numerical ranges described in the present invention and claims include the end values.

[0015] For the avoidance of doubt, the term "excess tin" should not be understood to exclude unintentional and unavoidable impurities in the manufacturing process. Lead-free, copper-free tin alloy From 100 wt% Weight Percent It should be understood that the composition is made by adding unavoidable impurities to tin.

[0016] Preferably, Lead-free, copper-free tin alloy contains 1.5 to 2.5 wt % of silver. Lead-free, copper-free tin alloy contains 1.75-2.25 wt% silver.

[0017] Preferably, Lead-free, copper-free tin alloy contains 2 to 3 wt% bismuth. More preferably, Lead-free, copper-free tin alloy contains 2.25-2.75 wt% bismuth.

[0018] Preferably, Lead-free, copper-free tin alloy contains 0.5 to 1.5 wt% of antimony. More preferably, Lead-free, copper-free tin alloycontains 0.75-1.25 wt% antimony.

[0019] Preferably, Lead-free, copper-free tin alloy More preferably, the nickel content is 0.045 to 0.055 wt %. Lead-free, copper-free tin alloy contains 0.0475-0.0525 wt% nickel.

[0020] Preferably, Lead-free, copper-free tin alloy More preferably, the above-mentioned mixture contains 0.005 to 0.015 wt% germanium. Lead-free, copper-free tin alloy contains 0.0075 to 0.0125 wt% germanium.

[0021] Preferably, bismuth and antimony Weight Percent The content of bismuth and antimony is preferably in the range of 1.0 to 4.5 wt%. Weight Percent The content of bismuth and antimony is preferably in the range of 3.0 to 4.0 wt%. Weight Percent The range of bismuth and antimony is 3.0 to 3.75 wt%. Weight Percent is in the range between 3.25 and 3.75 wt%. Effect of the Invention

[0022] As described above, the present invention has the following advantages. The present invention Lead-free, copper-free tin alloy contains 0.01-3.0 wt% silver, 0.01-5.0 wt% bismuth, 0-2.0 wt% antimony, 0.005-0.1 wt% nickel, 0.005-0.02 wt% germanium, and an excess amount of tin. Lead-free, copper-free tin alloy is capable of producing solder balls for ball grid array (BGA) packages, and Lead-free, copper-free tin alloy The resulting structure (eg, solder bump) after welding has excellent mechanical shock resistance, while at the same time having good weldability, ductility, oxidation resistance, and thermal cycling reliability.

[0023] Other features of the present invention will become apparent from the following detailed description of the present invention and the accompanying drawings. [Brief description of the drawings]

[0024] [Figure 1] 11 is a photograph illustrating slicing of a defective solder joint due to two solder balls formed in Comparative Example 1. [Diagram 2] 1 is a photograph illustrating a slice of a good solder joint formed in Example 1. [Diagram 3] 11 is a photograph illustrating the observation results when the ink-dyed area of ​​the solder joint formed in Comparative Example 1 exceeds 50% of the cross-sectional area. [Figure 4] 1 is a photograph illustrating the observation results when the ink-dyed area of ​​the solder joint formed in Example 1 does not exceed 50% of the cross-sectional area. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited thereto.

[0026] <Examples 1 to 11 and Comparative Examples 1 to 19> Lead-free, copper-free tin alloy was prepared. Examples 1 to 11 and Comparative Examples 1 to 9 Lead-free, copper-free tin alloy The metal components and Weight Percent Based on (wt%), the production was carried out through the following steps: Step (1): The corresponding metal component and Weight Percent Based on this, a corresponding metal material is prepared. Step (2): The prepared metal material is heated to melt and cast to produce the products of Examples 1 to 11 and Comparative Examples 1 to 9. Lead-free, copper-free tin alloy Form. [Table 1]

[0027] <Alloy property test> First, the points to be explained are as follows: Lead-free, copper-free tin alloy The weldability was evaluated by a thrust test, the ductility of the alloy was evaluated by a tensile test, the oxidation resistance was evaluated by a board level welding test, the thermal fatigue strength (i.e., reliability of thermal cycling) of the welds and joint structure was evaluated by a thermal cycle test, and the mechanical impact resistance (i.e., reliability against mechanical impact) of the welds and joint structure was evaluated by a mechanical impact test.

[0028] The test methods for the thrust test, board level weld test, thermal cycling test and mechanical shock test are described below.

[0029] <Thrust test> Ball diameter 0.45 mm Example or Comparative Example Lead-free, copper-free tin alloy The solder balls manufactured by the method were used to reball a ball grid array (BGA) element (the element size was 14 mm x 14 mm, and the peak temperature of the reball reflow curve was 240°C). After reballing was completed, a thrust test of the solder bumps was performed using a push-pull tester (the moving speed of the push cutter was 100 μm / s). Each set of alloy BGA samples pushed 15 solder bumps and the thrust strength was recorded. The average thrust strength of the 15 solder bumps was taken as the experimental result.

[0030] <Judgment criteria> If the average thrust strength exceeds 13 N, the reball weldability is judged to be good and marked with "O". If the average thrust strength is in the range of 11-13 N, the reball weldability is judged to be acceptable and marked with "△". If the average thrust strength is less than 11 N, the reball weldability is judged to be insufficient and marked with "X".

[0031] <Tensile test> Examples or Comparative Examples Lead-free, copper-free tin alloyTensile tests were conducted. The preparation and testing methods of tensile samples were in accordance with ASTM E8, the tensile speed was 6 mm / min, and the ductility of the alloys was compared based on the results of the elongation rate of the tensile test. In this test, three tensile samples were tested for each alloy, and the average value was obtained from the three elongation rate results.

[0032] <Judgment criteria> If the average elongation is greater than 25%, the alloy is judged to have good ductility and is marked with an "O". If the average elongation is between 20-25%, the alloy is judged to have acceptable ductility and is marked with a "△". If the average elongation is less than 20%, the alloy is judged to have insufficient ductility and is marked with an "X".

[0033] <Board level welding test> Ball diameter 0.63 mm Example or Comparative Example Lead-free, copper-free tin alloy The solder balls manufactured in the above were used to reball a ball grid array (BGA) element (the element size was 35 mm×35 mm, and the peak temperature of the reball reflow curve was 250° C.). After reballing was completed, the BGA element was first left at high temperature and high humidity (85° C. / 85% RH) for 240 hours, and then reflow welded to the corresponding circuit board sample (the peak temperature of the reflow curve was 245° C.). The purpose of this test was to Lead-free, copper-free tin alloy The purpose of this study is to test the oxidation resistance of solder bumps formed after reballing of solder balls manufactured by high temperature and humidity processing in board level processing. High temperature and humidity processing is used to accelerate the oxidation reaction of solder bumps on devices. The oxidation resistance of alloys affects the weldability when welding solder bumps to circuit boards. If the oxidation resistance of alloys is insufficient, the weldability will be insufficient when welding solder bumps to circuit boards, and the occurrence rate of double ball defects after board level processing will increase.

[0034] In this test, the incidence of double balls was analyzed by X-ray for samples after board level. The criteria for judgment are as follows: if the incidence of double balls is less than 10%, the weldability (i.e., anti-oxidation ability) at the board level is judged to be good and marked as "○". If the incidence of double balls is in the range of 10-20%, the weldability (i.e., anti-oxidation ability) at the board level is judged to be acceptable and marked as "△". If the incidence of double balls is more than 20%, the weldability (i.e., anti-oxidation ability) at the board level is judged to be unsuccessful and marked as "X".

[0035] <Thermal cycling test> Ball diameter 0.45 mm Example or Comparative Example Lead-free, copper-free tin alloy The ball grid array (BGA) element was reballed using the solder balls manufactured in the above (the element size was 14 mm×14 mm, and the peak temperature of the reballing reflow curve was 250° C.). After the reballing was completed, the BGA element was reflow welded to the corresponding circuit board sample (the peak temperature of the reflow curve was 245° C.), and the sample after the welding was completed was subjected to a thermal cycle test (the test conditions were -40 to 125° C., the temperature increase and decrease rates were 15° C. / min, the warming time was 10 minutes, and the cycle was performed a total of 600 times). Next, a red ink immersion test was performed on the sample after the thermal cycle was completed. The red ink immersion test method was to first immerse the sample in red ink, remove the element after the ink dried, and finally observe the cross section of the welded point after the element was removed under a microscope. Observations were performed on a total of 192 welded points of all elements of each sample. Lead-free, copper-free tin alloy A red ink immersion test was performed on a welded sample of one BGA element manufactured with solder balls of 192 pieces each, and a cross-section observation was performed on each of the 192 welded points. The purpose of this test was to Lead-free, copper-free tin alloyThe purpose of this test is to test the thermal fatigue strength of the solder ball welds and the joint structure between the welds and the copper base material. If the thermal fatigue strength of the alloy welds themselves and the joint structure with the copper base material is insufficient, the welds or the joint structure will be thermally fatigued and destroyed by the stress of repeated thermal cycling, which will affect the reliability of the welds. In this test, a red ink immersion test is performed on the samples after thermal cycling. If defects or fractures occur in the welds during the thermal cycling test, the ink staining phenomenon will occur on the cross section of the welds after the red ink immersion test. The degree and quantity of ink staining on the cross section of the welds indicate the degree and quantity of destruction that has occurred in the welds and the joint structure, and the ink staining conditions of the welds of different samples are compared to judge the thermal fatigue strength of the welds and the joint structure.

[0036] <Judgment criteria> If the ink-stained area of ​​all welds does not exceed 50% of the cross-sectional area, the thermal fatigue strength of the alloy welds and joint structure is judged to be good and marked with an "O". If the number of welds with an ink-stained area exceeding 50% is less than 10, the thermal fatigue strength of the alloy welds and joint structure is judged to be acceptable and marked with a "△". If the number of welds with an ink-stained area exceeding 50% is 10 or more, the thermal fatigue strength of the alloy welds and joint structure is judged to be insufficient and marked with an "X".

[0037] <Mechanical impact test> Ball diameter 0.45 mm Example or Comparative Example Lead-free, copper-free tin alloyThe solder balls manufactured in the above were used to reball a ball grid array (BGA) element (the element size was 14 mm×14 mm, and the temperature of the peak value of the reball reflow curve was 250° C.). After reballing was completed, the BGA element was reflow welded to the corresponding circuit board sample (the temperature of the peak value of the reflow curve was 245° C.), and the sample after welding was completed was subjected to a mechanical shock test (the test conditions were an acceleration of 1500 g, an impact dwell time of 0.5 ms, and a total of 50 impact tests were performed). Next, a red ink immersion test was performed on the sample after the mechanical shock test was completed. The red ink immersion test method was to first immerse the sample in red ink, remove the element after the ink dried, and finally observe the cross section of the welded point after the element was removed under a microscope, and observation was performed on a total of 192 welded points of all elements of each sample. Lead-free, copper-free tin alloy A red ink immersion test was performed on a welded sample of one BGA element manufactured with solder balls of 192 pieces each, and a cross-section observation was performed on each of the 192 welded points. The purpose of this test was to Lead-free, copper-free tin alloy The purpose of this test is to test the mechanical impact resistance of the solder bump welds formed after reballing of the solder balls and the joint structure between the bump welds and the copper base material. If the mechanical impact resistance of the alloy welds themselves and the joint structure with the copper base material is insufficient, the welds or the joint structure cannot withstand the mechanical impact force and are destroyed, which affects the reliability of the welds. In this test, a red ink immersion test is performed on the samples after the mechanical impact test. If defects or fractures occur in the welds during the mechanical impact test, the ink staining phenomenon occurs on the cross section of the welds after the red ink immersion test. The degree and quantity of ink staining on the cross section of the welds indicate the degree and quantity of destruction that has occurred in the welds and the joint structure, and the mechanical impact resistance of the welds and the joint structure is judged by comparing the ink staining conditions of the welds of different samples.

[0038] <Judgment criteria> If the ink-stained area of ​​all welds does not exceed 50% of the cross-sectional area, the mechanical impact resistance of the alloy welds and joint structure is judged to be good and marked with an "O". If the number of welds with ink-stained area exceeding 50% is less than 10, the mechanical impact resistance of the alloy welds and joint structure is judged to be acceptable and marked with a "△". If the number of welds with ink-stained area exceeding 50% is 10 or more, the mechanical impact resistance of the alloy welds and joint structure is judged to be insufficient and marked with an "X".

[0039] Next, Comparative Example 1 and Example 1 of the present invention will be described in more detail with reference to Figures 1 to 4. Figure 1 is a photograph explaining a slice of a defective solder joint due to two solder balls formed in Comparative Example 1. Figure 2 is a photograph explaining a slice of a normal solder joint formed in Example 1. Figure 3 is a photograph explaining an observation result when the ink-dyed area of ​​the solder joint formed in Comparative Example 1 exceeds 50% of the cross-sectional area. Figure 4 is a photograph explaining an observation result when the ink-dyed area of ​​the solder joint formed in Example 1 does not exceed 50% of the cross-sectional area.

[0040] Also, it should be noted that the same embodiment or the same comparative example is subjected to the four tests, namely the thrust test, board level welding test, thermal cycle test, and mechanical impact test, and if there is even one "X" in the test results, the "Overall Evaluation Result" column in Table 1 is marked with "X", indicating that this embodiment or comparative example does not meet the requirements of the present invention. If there is even one "△" in the test results, the "Overall Evaluation Result" column in Table 1 is marked with "△", indicating that this embodiment or comparative example meets the requirements of the present invention. If all three test results are "○", the "Overall Evaluation Result" column in Table 1 is marked with "○", indicating that this embodiment not only meets the requirements of the present invention but is also the best embodiment.

[0041] <Test results and discussion of alloy properties> The following discussion will be based on the results obtained with different silver contents, different bismuth contents, different antimony contents, different nickel contents, different germanium contents, and different copper contents.

[0042] [Table 2]

[0043] As can be seen in Figure 2, the silver Weight Percent It affects the tensile test results (i.e., the ductility of the alloy), the thermal fatigue strength (i.e., the reliability of thermal cycling) and the mechanical shock resistance (i.e., the reliability of mechanical shock) of the alloy welds and joint structures. Weight Percent If is too low, Lead-free, copper-free tin alloy will not be able to pass the thermal cycling test. Weight Percent If is too high, Lead-free, copper-free tin alloy will not be able to pass tensile tests and mechanical impact tests.

[0044] Comparative Example 1 does not contain silver and the thermal cycling test is marked with an "X"; Weight Percent The silver content is too low (less than 0.01 wt%), which indicates that the alloy lacks thermal cycling reliability. Comparative Example 2 uses 4.0 wt% silver, and the tensile test and mechanical impact test are marked with "X", which indicates that the silver content is too low (less than 0.01 wt%), which indicates that the alloy lacks thermal cycling reliability. Weight Percent This indicates that the alloy's ductility and reliability against mechanical shock are insufficient because the content of silver is too high (over 3.0 wt%). Example 2 uses 0.01 wt% silver, Example 1 uses 2.0 wt% silver, and Example 3 uses 3.0 wt% silver. All of these are marked as "△" or "○" in the "Overall Evaluation Result" column in Table 2. Lead-free, copper-free tin alloy This shows that the requirements of the present invention are met by containing 0.01 to 3.0 wt % of silver therein.

[0045] [Table 3]

[0046] As can be seen from Figure 3, the bismuth Weight Percent affects the tensile test results of the alloy (i.e., the ductility of the alloy), the thermal fatigue strength (i.e., the reliability of thermal cycling) and the mechanical shock resistance (i.e., the reliability of mechanical shock) of the alloy's welds and joint structures. Weight Percent If is too low, Lead-free, copper-free tin alloy will not be able to pass the thermal cycling test. Weight Percent If is too high, Lead-free, copper-free tin alloy will not be able to pass tensile tests and mechanical impact tests.

[0047] Comparative Example 3 does not contain bismuth and is marked with an "X" for the thermal cycling test. Weight Percent The results of the tensile test and mechanical impact test are marked with "X" in Comparative Example 4, which uses 6.0 wt% bismuth, and the thermal cycling reliability of the alloy is insufficient because the bismuth is too low (less than 0.01 wt%). Weight Percent This indicates that the alloy's ductility and reliability against mechanical shock are insufficient because the content of bismuth is too high (over 5.0 wt%). Example 4 uses 0.01 wt% bismuth, Example 1 uses 2.5 wt% bismuth, and Example 5 uses 5.0 wt% bismuth. All of these are marked as "△" or "○" in the "Comprehensive Evaluation Result" column in Table 3. Lead-free, copper-free tin alloy It is shown that the requirements of the present invention are met by containing 0.01 to 5.0 wt% of bismuth therein.

[0048] [Table 4]

[0049] As can be seen from Figure 4, the antimony Weight Percent influences thrust test results (i.e. weldability), tensile test results (i.e. alloy ductility), thermal fatigue strength (i.e. thermal cycling reliability) and mechanical shock resistance (i.e. reliability against mechanical shock) of welds and joint structures. Weight Percent If is low, Lead-free, copper-free tin alloy is acceptable during thermal cycling testing. Weight Percent If is too high, Lead-free, copper-free tin alloywill not be able to pass thrust tests, tensile tests and mechanical impact tests.

[0050] In Comparative Example 5, 3.0 wt% antimony was used, and the thrust test, tensile test, and mechanical impact test are marked with "X"; Weight Percent This indicates that the alloy is insufficient in weldability, ductility, and reliability against mechanical impact because the antimony content is too high (over 2.0 wt%). Example 6 uses 0 wt% antimony, Example 1 uses 1.0 wt% antimony, and Example 7 uses 2.0 wt% antimony. All of these are marked with "△" or "○" in the "Comprehensive Evaluation Result" column in Table 4. Lead-free, copper-free tin alloy It is shown that the requirements of the present invention are met by containing 0 to 2.0 wt % of antimony therein.

[0051] [Table 5]

[0052] As can be seen from Figure 5, Weight Percent This indicates that the effects of nickel on the thermal fatigue strength (i.e., reliability in thermal cycling) and mechanical shock resistance (i.e., reliability against mechanical shock) of the alloy welds and joint structures. Weight Percent is too low, Lead-free, copper-free tin alloy The nickel will not be able to pass the thermal cycling test. Weight Percent If is too high, Lead-free, copper-free tin alloy will not be able to pass mechanical shock tests.

[0053] Comparative Example 6 does not contain nickel and is marked with an "X" for the thermal cycling test. Weight Percent The alloy is not reliable in thermal cycling because the content of nickel is too low (less than 0.005 wt%). Comparative Example 7 uses 0.2 wt% nickel, and the mechanical shock test is marked with "X". Weight PercentThis indicates that the alloy is not reliable against mechanical shock because the content of nickel is too high (over 0.1 wt%). Example 8 uses 0.005 wt% nickel, Example 1 uses 0.05 wt% nickel, and Example 9 uses 0.1 wt% nickel. All of these are marked as "△" or "○" in the "Overall Evaluation Result" column of Table 5. Lead-free, copper-free tin alloy This shows that the requirements of the present invention are met by containing 0.005 to 3.1 wt% of nickel therein.

[0054] [Table 6]

[0055] As can be seen from Figure 6, the germanium Weight Percent influences the thrust test results (i.e., weldability) and board level weld test results (i.e., oxidation resistance) of the alloy. Weight Percent If is too low, Lead-free, copper-free tin alloy Germanium will not be able to pass the board level welding test. Weight Percent If is too high, Lead-free, copper-free tin alloy will not be able to pass the thrust test.

[0056] Comparative Example 8 does not contain germanium and is marked with an "X" in the board level weld ring test. Weight Percent The low oxidation resistance (less than 0.005 wt%) of the alloy indicates the alloy lacks oxidation resistance. Comparative Example 9 uses 0.05 wt% germanium, and the thrust test is marked with an "X". Weight Percent The high value (>0.02 wt%) indicates that the weldability of the alloy is insufficient. Example 10 uses 0.005 wt% germanium, Example 1 uses 0.01 wt% germanium, and Example 11 uses 0.02 wt% germanium. All of these are marked with "△" or "○" in the "Overall Evaluation Result" column of Table 6. Lead-free, copper-free tin alloy It is shown that the requirements of the present invention are met by containing 0.005 to 0.02 wt % of germanium therein.

[0057] <Conclusion> Based on the above results and discussion, Examples 1 to 11 Lead-free, copper-free tin alloy In the "Overall Evaluation Result" column, all of the results are marked with "△" or "◯", which indicates that the thrust test, board level welding test, thermal cycle test, and mechanical shock test are all passed simultaneously. Lead-free, copper-free tin alloy (See Examples 1 to 11) to manufacture solder balls for use in ball grid array (BGA) packages. Lead-free, copper-free tin alloy The resulting structure (eg, solder bump) after welding has excellent mechanical shock resistance, while also having good weldability, ductility, oxidation resistance, and thermal cycling reliability.

[0058] In summary, the present invention Lead-free, copper-free tin alloy contains 0.01-3.0 wt% silver, 0.01-5.0 wt% bismuth, 0-2.0 wt% antimony, 0.005-0.1 wt% nickel, 0.005-0.02 wt% germanium, and an excess amount of tin at the same time, Lead-free, copper-free tin alloy is capable of producing solder balls for use in ball grid array (BGA) packages, and Lead-free, copper-free tin alloy The structure (e.g., solder bump) obtained after welding has excellent reliability against mechanical shock, and at the same time, has good weldability, ductility, oxidation resistance, and thermal cycling reliability, thereby reliably achieving the object of the present invention.

[0059] Although the present invention has been described above using the embodiments, the technical scope of the present invention is not limited to the scope described in the above embodiments. It is clear to those skilled in the art that various modifications and improvements can be made to the above embodiments. It is clear from the description of the claims that such modifications and improvements can also be included in the technical scope of the present invention.

Claims

1. A lead-free, copper-free tin alloy, the weight percentage of which is calculated as 100 wt%; 1.5-2.5 wt% silver; 0.01 to 2.5 wt% bismuth; 0-2.0 wt% antimony; 0.005 to 0.1 wt% nickel; 0.005 to 0.02 wt% germanium; and an excess amount of tin.

2. 2. The lead-free, copper-free tin alloy of claim 1, wherein the lead-free, copper-free tin alloy contains 0.5 to 1.5 wt % antimony.

3. 2. The lead-free, copper-free tin alloy of claim 1, wherein the lead-free, copper-free tin alloy contains 0.045 to 0.055 wt % nickel.

4. 2. The lead-free, copper-free tin alloy of claim 1, wherein the lead-free, copper-free tin alloy contains 0.005 to 0.015 wt % germanium.

5. 2. A solder ball for a ball grid array package, which is made of the lead-free, copper-free tin alloy according to claim 1.

Citation Information

Patent Citations

  • Solder alloy

    JP2000280090A

  • Lead-free solder alloy

    JP2003094195A

  • Lead-free solder alloy, electronic circuit board and electronic control device

    JP2018001179A

  • Solder paste for chip component joining

    JP2019155465A

  • Lead-free and copper-free-based tin alloy, and solder ball using BGA package

    JP2021109229A